Analisis Pengawasan Pelaksanaan Kewajiban Perpajakan Wajib Pajak Badan Dalam Meningkatkan Kepatuhan Wajib Pajak Di Kpp Pratama Bekasi Barat Tahun 2021 - 2022 - Dessy Nuur’Aini; Jiwa Pribadi Agustianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Tax payments are one of the manifestations of state obligations and taxpayer participation to directly and jointly carry out the taxation obligations of state financing and national development. Supervision of Taxpayer Compliance is one of the important things to consider in the intensification and extensification of tax revenue. Account Representative (AR) is responsible for all taxpayers in their region in order to pay taxes and submit SPT to the Tax Service Office. This research was conducted at the West Bekasi Pratama KPP using a descriptive qualitative approach and the data obtained was the result of interviews with resource persons and documentation. The results of this study can be concluded that the lack of maximum in supervision despite monitoring of the target to be achieved. In its implementation there are obstacles from internal and external, namely the number of human resources that are not proportional to the number of taxpayers and the level of awareness of taxpayers is still low. To overcome the obstacles that occur, fiscus efforts must be proactive in providing education to the community by providing evidence of how important taxes can be felt by the community, and need to improve the quality of human resources and infrastructure.